RNA- and miRNA-interference to enhance abiotic stress tolerance in plants - Ruby Tiwari; Manchikatla Venkat Rajam (Journal of Plant Biochemistry and Biotechnology, 2022)

Shoreline Change Analysis Using Historical Multispectral Landsat Images of the Pacific Coast of Panama - Ruby Vallarino Castillo; Vicente Negro Valdecantos; Luis Moreno Blasco (Journal of Marine Science and Engineering, 2022)
The shoreline is the interface between sea and land influenced by natural, anthropogenic factors and climate change. The study of the evolution of the shoreline provides information to evaluate accretion or erosion processes. Shoreline erosion represents a threat to the safety of the coastal population, reducing the extension of the beach zone and making human settlements vulnerable to extreme events. This research presents the analysis of the evolution of the shoreline by multispectral images from Landsat satellites and the Digital Shoreline Analysis System (DSAS) of the Pacific Coast of Panama for the period of 1998–2021. The automated shoreline extraction was generated by combining remote sensing techniques, such as the Histogram Threshold Method and the Band Ratio Method, to generate binary images delineating the land and water zone. The most vulnerable zone, due to erosion processes and the exposition of urban areas, corresponds to the zone of Serena beach and Coronado beach with an average negative distance movement of −23.95 m. Finally, it was concluded that there is a general tendency of erosion processes in the study zone with a rate for long-term analysis of −1.12 m/y (zone I), −1.01 m/y (zone II), and −1.08 m/y (zone III).

Plasma and muscle tissue disposition of enrofloxacin in Nile tilapia ( Oreochromis niloticus ) after intravascular, intraperitoneal, and oral administrations - Orhan Corum; Ertugrul Terzi; Duygu Durna Corum; Yigit Tastan; Ruby C. Gonzales; Osman Nezih Kenanoglu; Dan M. Arriesgado; Victor R. Navarro; Soner Bilen; Adem Yavuz Sonmez; Kamil Uney (Food Additives & Contaminants: Part A, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Seaweed ethnobotany of eastern Sorsogon, Philippines - Richard V. Dumilag; Teresa Haide R. Belgica; Lynn C. Mendoza; Janet M. Hibay; Abel E. Arevalo; Mark Ariel D. Malto; Elden G. Orgela; Mabille R. Longavela; Laurence Elmer H. Corral; Ruby D. Olipany; Caesar Franz C. Ruiz; Cynthia B. Mintu; et al. (Algae, 2022)
Knowledge on the seaweeds of eastern Sorsogon in the Philippines is uneven. Not only is eastern Sorsogon among the areas of high seaweed diversity but locals there have interacted with seaweeds for ages. Despite seaweeds’ assumed importance to Sorsoganon, ethnobotanical records are missing. In this study, we documented the traditional knowledge on seaweed use and determined the rate of knowledge transmission among the locals of eastern Sorsogon. Vernacular names and modes of preparation were given of the 12 identified species bearing culinary and medicinal importance. Ten species were eaten while three were used therapeutically. Based on ethnobotanical indices, Caulerpa chemnitzia ecad turbinata and Gelidiella acerosa were the most important seaweeds. The least cited was Caulerpa racemosa. Our study demonstrated that most of the seaweed resources in eastern Sorsogon remain largely untapped, as the identified ethnotaxa were only about 5% of the total seaweed species diversity reported for the area. The seaweed knowledge in eastern Sorsogon appeared to be homogenous across age groups with primary sources of knowledge biased towards female relatives (mothers and grandmothers) and to children as inheritors. Cessation of seaweed knowledge may come at a potential cost, as a significant fraction of the population did not transmit their knowledge to others. Our study furthered the interest in providing sophisticated resource management recommendations that consider the relationships of traditional and scientific knowledge of seaweed selection and use in eastern Sorsogon and beyond.

Analysis of positive correlation in magnitude and time measurement for earthquake using electric signals - Oumaima Saidani; Ramkumar Raja Manoharan; Ahmed Samir Naje; Ruby Mishra; Arjun Subburaj; Maheswari S; Mohamed Yacin Sikkandar; Sankar Ganesh Sundaram; Regin Rajan; Sudhakar Sengan (Earth Science Informatics, 2022)

Antimicrobial, antioxidant, antiviral activity, and gas chromatographic analysis of Varanus griseus oil extracts - Shakeel Ahmad; Tahira Ruby; Mirza Imran Shahzad; Gildardo Rivera; Diana Victoria Navarrete Carriola; Aleem Ahmed Khan (Archives of Microbiology, 2022)

Detecting genetic epistasis by differential departure from independence - Ruby Sharma; Zeinab Sadeghian Tehrani; Sajal Kumar; Mingzhou Song (Molecular Genetics and Genomics, 2022)

Climate shapes community flowering periods across biomes - Ruby E. Stephens; Hervé Sauquet; Greg R. Guerin; Mingkai Jiang; Daniel Falster; Rachael V. Gallagher (Journal of Biogeography, 2022)
Aim Climate shapes the composition and function of plant communities globally, but it remains unclear how this influence extends to floral traits. Flowering phenology, or the time period in which a species flowers, has well‐studied relationships with climatic signals at the species level but has rarely been explored at a cross‐community and continental scale. Here, we characterise the distribution of flowering periods (months of flowering) across continental plant communities encompassing six biomes, and determine the influence of climate on community flowering period lengths. Location Australia. Taxon Flowering plants. Methods We combined plant composition and abundance data from 629 standardised floristic surveys (AusPlots) with data on flowering period from the AusTraits database and additional primary literature for 2983 species. We assessed abundance‐weighted community mean flowering periods across biomes and tested their relationship with climatic annual means and the predictability of climate conditions using regression models. Results Combined, temperature and precipitation (annual mean and predictability) explain 29% of variation in continental community flowering period. Plant communities with higher mean temperatures and lower mean precipitation have longer mean flowering periods. Moreover, plant communities in climates with predictable temperatures and, to a lesser extent, predictable precipitation have shorter mean flowering periods. Flowering period varies by biome, being longest in deserts and shortest in alpine and montane communities. For instance, desert communities experience low and unpredictable precipitation and high, unpredictable temperatures and have longer mean flowering periods, with desert species typically flowering at any time of year in response to rain. Main conclusions Current climate conditions shape flowering periods across biomes, with implications for phenology under climate change. Shifts in flowering periods across climatic gradients reflect changes in plant strategies, affecting patterns of plant growth and reproduction as well as the availability of floral resources for pollinators across the landscape.

Small herbivores with big impacts: Tundra voles ( Microtus oeconomus ) alter post‐fire ecosystem dynamics - Jess K. Steketee; Adrian V. Rocha; Laura Gough; Kevin L. Griffin; Ian Klupar; Ruby An; Nicole Williamson; Rebecca J. Rowe (Ecology, 2022)
Fire is an important ecological disturbance that can reset ecosystems and initiate changes in plant community composition, ecosystem biogeochemistry, and primary productivity. As herbivores rely on primary producers for food, changes in vegetation may alter plant–herbivore interactions with important—but often unexplored—feedbacks to ecosystems. Here we examined the impact of post‐fire changes in plant community composition and structure on habitat suitability and rodent herbivore activity in response to a large, severe, and unprecedented fire in northern Alaskan tundra. In moist acidic tundra where the fire occurred, tundra voles ( Microtus oeconomus ) are the dominant herbivore and rely on the tussock forming sedge Eriophorum vaginatum for both food and nesting material. Tundra voles were 10 times more abundant at the burned site compared with nearby unburned tundra 7‐12 years after the fire. Fire increased the habitat suitability for voles by increasing plant productivity and biomass, food quality, and cover through both taller vegetation and increased microtopography. As a result of elevated vole abundance, Eriophorum mortality caused by vole herbivory was two orders of magnitude higher than natural mortality and approached the magnitude of the mortality rate resulting directly from the fire. These findings suggest that post‐fire increases in herbivore pressure on Eriophorum could, in turn, disrupt graminoid recovery and enhance shrub encroachment. Tundra state transitions from graminoid to shrub dominated are also evident following other disturbances and fertilization experiments, suggesting that as Arctic temperatures rise, greater available nutrients and increased frequencies of large‐scale disturbances may also alter plant–animal interactions with cascading impacts on plant communities and ecosystem function.

Alkali-activated concretes based on high unburned carbon content fly ash: carbonation and corrosion performance - William G. Valencia-Saavedra; Ana María Aguirre-Guerrero; Ruby Mejía de Gutiérrez (European Journal of Environmental and Civil Engineering, 2022)

Integrated Nutrient Management in Coconut (Cocos nucifera L.): an Assessment of Soil Chemical and Biological Parameters Under Subtropical Humid Climate - Deepak Kumar; Rajiv Rakshit; Ruby Rani; Pallavi Bharti; Anupam Das; Manoj Kundu (Journal of Soil Science and Plant Nutrition, 2022)

Enhancement of output power of semitransparent photovoltaic thermal air collector using ANFIS model - Ruby Beniwal; Narendra Singh Beniwal; Hari Om Gupta (Environmental Science and Pollution Research, 2022)

Urbanization Impact on Regional Climate and Extreme Weather: Current Understanding, Uncertainties, and Future Research Directions - Yun Qian; T. C. Chakraborty; Jianfeng Li; Dan Li; Cenlin He; Chandan Sarangi; Fei Chen; Xuchao Yang; L. Ruby Leung (Advances in Atmospheric Sciences, 2022)
Urban environments lie at the confluence of social, cultural, and economic activities and have unique biophysical characteristics due to continued infrastructure development that generally replaces natural landscapes with built-up structures. The vast majority of studies on urban perturbation of local weather and climate have been centered on the urban heat island (UHI) effect, referring to the higher temperature in cities compared to their natural surroundings. Besides the UHI effect and heat waves, urbanization also impacts atmospheric moisture, wind, boundary layer structure, cloud formation, dispersion of air pollutants, precipitation, and storms. In this review article, we first introduce the datasets and methods used in studying urban areas and their impacts through both observation and modeling and then summarize the scientific insights on the impact of urbanization on various aspects of regional climate and extreme weather based on more than 500 studies. We also highlight the major research gaps and challenges in our understanding of the impacts of urbanization and provide our perspective and recommendations for future research priorities and directions.

First report of fruit rot of jackfruit caused by Athelia rolfsii in India - Abdulmajeed Sajeena; Deepu Mathew; Jacob John; M. K. Dhanya; K. Sushitha; P. Ruby Nahan (Journal of Plant Pathology, 2022)

Hydrogen Sulfide Production with a Microbial Consortium Isolated from Marine Sediments Offshore - Roberto Briones-Gallardo; Muriel González-Muñoz; Itza García-Bautista; David Valdés-Lozano; Tanit Toledano-Thompson; Erik Polanco-Lugo; Renata Rivera-Madrid; Ruby Valdez-Ojeda (Journal of Marine Science and Engineering, 2022)
Hydrogen, electric energy production, and metal toxic bioremediation are some of the biotechnological applications of sulfate-reducing organisms, which potentially depend on the sulfide produced. In this study, offshore of Yucatan, the capacity to produce hydrogen sulfide using microbial consortia from marine sediment (SC469, PD102, SD636) in batch reactors was evaluated. Kinetic tests were characterized by lactate oxidation to acetate, propionate, CO2 and methane. The inoculum SC469, located in open-ocean, differed strongly in microbial diversity and showed better performance in substrate utilization with the highest hydrogen sulfide production (246 mmolg−1 VSS) at a specific hydrogen sulfide rate of 113 mmol g−1 VSS d−1 with a 0.79 molar ratio of sulfate/lactate. Sulfate-reducing microbial consortia enriched in the laboratory from marine sediments collected offshore in Yucatan and with a moderate eutrophication index, differed strongly in microbial diversity with loss of microorganisms with greater capacity for degradation of organic macromolecules. The sulfate-reducing microorganisms were characterized using Illumina MiSeq technology and were mainly Desulfomicrobium, Clostridium and Desulfobacter.

Phytochemicals, nutritional, antioxidant activity, and sensory analyses of Moringa oleifera Lam. collected from mid-hill region of Nepal - Yadav Kc; Ruby Rai; Nirat Katuwal; Lila Devi Shiwakoti; Bhoj Raj Pant; Tirtha Raj Bajgai; Srijana Dura; Dhiraj Kumar Chaudhary; Vijaya Raghavan; Jitendra Upadhyaya (Natural Product Research, 2022)

A comprehensive review of dye-sensitized solar cell optimal fabrication conditions, natural dye selection, and application-based future perspectives - Ruby Baby; Peter Daniel Nixon; Nallapaneni Manoj Kumar; M. S. P. Subathra; Nallamuthu Ananthi (Environmental Science and Pollution Research, 2022)